A new value chain model for the evolution of broadband application market. (28th July 2006) - Ng, P.T. Andy; Lu, Dawei; Li, C.K.; Chan, H.Y. Harry
The market of advanced broadband applications is currently underdeveloped because of some unique technical features of the internet and the existing value chain models cannot guarantee satisfactory application performance to the users. This paper aims to solve the problem from the perspective of industrial organisation. We propose a new value chain model to facilitate commercial development of the broadband application market. It emphasises coordination by demand chain management between all sectors in the value chain to deliver end-to-end Quality of Service (QoS) for broadband applications. We propose a way to implement the new value chain model at the operational level by the availability of enabling technology and a demand-oriented bandwidth management framework. The framework considers user perception and Human-Computer Interaction (HCI) as the common demand characteristics. It includes an HCI-based classification framework to prioritise different broadband applications and a perception-based methodology to determine the optimal bandwidth allocation for individual application.